The environmental impact of the Copper industry in the Fani River Valley (Repsi "Hot spot") Mirdita, Albania - Daci, A.; Kaza, G.; Deda, T.; Hoti, S. (Bulletin of the Geological Society of Greece, 2007)
For more than 40 years, full cycle Copper industry has exercised its activity in central Mirdita, as one of the priorities for the economic development of this zone. Copper deposits have been discovered in many parts of the territory of central Mirdita, whereas the main activity of the mining and processing industry is located in the Fan iriver valley. The interruption of industrial activity after the years ’90, could not stop the negative environmental impact. The presence of dumps in Fani river banks (as in Repsi, Rresheni and Rubiku) and numerous mining works· (addits) in Spaçi and Kodër Spaçi slopes, from which many acid waters drain, including also the natural leaching of surface outcrops of mineralized zones, make up a serious danger to the biodiversity of this area. Several recommendations to reduce the environmental impact of the tailings and copper ores in the dumps in Fani river valley are given in this paper